Cross-sectional study of hepatitis B immunity in MSM between 2002 and 2012. (6th August 2013) - Gamagedara, Nimal; Weerakoon, Ajith P; Zou, Huachun; Fehler, Glenda; Chen, Marcus Y; Read, Tim RH; Bradshaw, Catriona S; Fairley, Christopher K
Abstract : Objectives: Incidence of hepatitis B has not been well studied recently in men who have sex with men (MSM) despite increases in sexual risk practices and other sexually transmitted infections. Our aim was to determine the incidence of hepatitis B infection among MSM and level of immunity to hepatitis B attending a sexual health service over 10 years. Methods: A cross-sectional analysis of all MSM attending Melbourne Sexual Health Centre (MSHC) from 1 July 2002 and 30 June 2012, and a retrospective cohort study of MSM who had attended MSHC on multiple occasions who had hepatitis serology done more than once. Results: Of 10 031 MSM attending the clinic, 58.4% (95% CI 57.4% to 59.4%) (5655/9677) had hepatitis B surface antibody (HepBsAb), 10.6% (95% CI 10.0% to 11.4%) (840/7888) had core antibody (HepBcAb), and 3.7% (95% CI 3.0% to 4.5%) (95/2577) had surface antigen (HepBsAg). The proportion with HepBsAb decreased from 72% to 48% (p (trend)<0.001), with HepBcAb decreased from 12% to 8% (p (trend)=0.039) and with either HepBsAb or HepBcAb, decreased from 67% to 50% (p (trend)<0.001) from 2002 to 2012, but did not change for HepBsAg (p (trend)=0.08). Seven cases of hepatitis B occurred in 3540 person-years of observation, giving an incidence of 1.98 (95% CI 0.79 to 4.07) per 1000 person-years. Conclusions: The data suggest that the current level of immunity of about 50% has been sufficient to prevent any significant hepatitis B infection in the last 10 years. Continued high levels of vaccination are important for prevention.